Implementing Character Education in Higher Education Institutions Through Science Learning - Destiani; Amrina Izzatika; Yoga Fernando Rizqi (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
One issue identified in this study pertains to the limited scope of character education, which tends to be predominantly focused on Islamic Religion and Pancasila Education Courses. Meanwhile, the Merdeka Belajar-Kampus Merdeka (MBKM) program has emerged as a significant force in promoting character education throughout the educational continuum from elementary to higher education levels. Hence, applying education and character values is imperative in science education within the Elementary School Teacher Education Study Program (PGSD) at the Faculty of Teacher Training and Education (FKIP) in Universitas Lampung. This research aims to describe what characteristics are implemented in the Lesson Plan (RPS) in science courses. The present study uses a descriptive qualitative approach to analyze the learning outcomes subs and learning indicators, afterward aligning them with 18-character values. The values encompassed are religiousness, honesty, tolerance, discipline, hard work, creativity, independence, democracy, curiosity, national spirit, love of the country, respect for achievements, friendliness, love of peace, love of reading, care for the environment, social care, and responsibility. Based on the research results, the 18-character values are spread across learning outcomes subs and students’ learning experience activities while attending science lectures at the PGSD Study Program FKIP UNILA. The implementation of character education has the potential to instill students who possess not only academic proficiency but also exhibit humanitarian attitudes towards their peers, as well as foster a sense of mutual respect and cooperation among themselves. Based on the RPS, the science courses used at the UNILA PGSD study program are very suitable for forming students' personality traits. As suggested by the researchers based on the findings they found, religious aspects should be added to RPS because this can be internalized in students and implemented in life.